The Influence of Customer Experience and Customer Satisfaction on Purchasing Decisions with Purchase Intention as an Intervening Variable in the My Pertamina Application - Andi Musniwan Kasman; Atika Tahir (LP2M IAIN Palopo, 2025)
This study aims to investigate the influence of customer experience and customer satisfaction on purchasing decisions, with purchase intention as a mediating variable, focusing on the MyPertamina application for purchasing subsidized fuel in Palopo City, Indonesia. Using a quantitative design with 100 respondents selected through incidental sampling, this study used a questionnaire and analyzed the data with SmartPLS 4.1 to test the outer and inner models. The study findings revealed that customer experience directly influences purchasing decisions but does not significantly influence purchase intention, while customer satisfaction significantly influences both purchase intention and purchase decision. In addition, purchase intention strongly mediates the relationship between customer satisfaction and purchase decision but does not mediate the relationship between customer experience and purchase decision. This suggests that while user experience directly contributes to purchasing behavior, satisfaction drives intention, which then shapes actual decisions. This study provides theoretical implications by integrating behavioral models in the context of digital public services and offers practical insights for application developers and policymakers to improve service efficiency, trust, and user satisfaction. However, its limitations include focusing only on one geographic region and application, which limits the generalizability of the findings. Future research should explore comparative contexts or incorporate qualitative approaches to capture deeper user perceptions and behavioral nuances. Overall, this study enriches the understanding of consumer decision-making patterns in adopting government-supported digital platforms.